Problem Solving Ability Based Curiousity Through Assistance and CPS Learning Assisted with Ethnomathematics Nuanced Modules - Barata, Agriat; Mastur, Zaenuri; Sukestyarno, Y.L (Unnes Journal of Mathematics Education Research, 2019)
This study aims to (1) determine the effectiveness of creative problem solving (CPS) learning assisted with Ethnomathematics nuanced modules on problem solving abilities (2) find out the differences in problem solving abilities of students with CPS learning assisted with Ethnomathematics nuanced modules (experiment 1), CPS module assistance classes Ethnomathematics nuance and control class (experiment 2), (3) describe problem solving ability based on curiosity of students in CPS learning class assisted with Ethnomathematics nuanced modules. This study applied a mixed method with concurrent embedded design. Quantitative data was obtained through questionnaires and tests that were analyzed by using the t-test and regression. Qualitative data was obtained through documentation and interviews of subjects selected based on the level of curiosity. Based on the results of the study obtained (1) CPS learning assisted with Ethnomathematics nuanced modules effectively improve the problem solving abilities. (2) there are differences in problem solving abilities in experimental class 1, experiment 2 and control class (3) Qualitative analysis of this study explained that students with high curiousity were able to complete 4 stages of problem solving, meanwhile, students with low and moderate curiosity have varying abilities but less good in completing the implementation phase of the completion plan. Students with low curiosity are not good at planning completion plans.